The moderating role of corporate social responsibility in determining Islamic Bank Margin - Handayani, Yuniorita Indah; Fadah, Isti; Utami, Elok Sri; Sumani, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The ability to generate profit is the most important factor for a bank. One of the indicators to asses bank profitability is Bank Margin which is influenced by internal and external factors. However, the survival of a bank does not only depend on the profitability, but also depends on its responsibility to the stakeholders including the community. Islamics bank are obliged to distribute some of their profits to support Corporate Social Responsibility (CSR) and disclose those activities in the bank annual report. This study aims to analyze internal factors that determining Islamic Bank Margin in Malaysia. The internal factors include capital, assets quality, management, earning and liquidity. This study further investigates the moderating role of CSR on the relationship between capital, asset quality, management, earning, liquidity and bank margins. The sample used are 10 Malaysian Islamic Banks. The method used is multiple regression. The findings show that 75.8% of Islamics Bank Margin is influenced by capital, asset quality, management, earning and liquidity. Partially, assets quality and earning significantly influence on Islamic Bank Margin, while capital, management and liquidity have no effect on bank margins. In addition, CSR is the potential variable to moderate the influence of capital, asset quality, management, and liquidity on Bank Margins.